ANALYSIS OF STUDENTS' MATHEMATICAL CREATIVE THINKING ABILITIES WITH CROSS-CULTURAL EXPERIENCES FROM DIFFERENT COUNTRIES AT SEKOLAH INDONESIA KUALA LUMPUR (SIKL) - Nabilah, Nafisyah Alfiyanti; Lailiyah, Siti; Taufik, Taufik; Mariani, Dewi (Jurnal Pendidikan Matematika dan IPA, 2025)
This research is based on the existing problems of students with different previous educational backgrounds in secondary schools (SMP) at the Sekolah Indonesia Kuala Lumpur (SIKL) related to mathematical creative thinking ability. Therefore, this research aims to describe students' mathematical creative thinking abilities with cross-cultural experiences from different countries experiences at SIKL. The type of research is descriptive with a qualitative approach. The subject of this research is students of class X at SIKL, Malaysia, in the 2023/2024 academic year, a total of 6 people will be categorized into two criteria that is students graduated from secondary school in Indonesia and graduated from secondary school outside Indonesia. The data collection technique in this research uses a written test on exponents and unstructured interviews. The data analysis technique used in this research is the qualitative descriptive analysis technique developed by Miles and Huberman. The data analysis techniques used in this research are reduction, display data, and conclusion. . In this research, the indicators of creative thinking ability used consist of four: fluency, flexibility, originality, and elaboration. The results of the research showed the creative thinking ability of students with secondary education backgrounds in Indonesia was at a medium level with the highest average in the fluency aspect. In contrast, students with school backgrounds outside Indonesia were at a medium level with the highest average in the originality aspect.